Students Perception On The Use Of Tiktok For Learning Speaking English - Diana Sarkila; Muhammad Hifdil Islam; Ririn Fatmawati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In summary, the comprehensive analysis of students' responses to 11 distinct questions about the utilization of TikTok as a learning medium in English-speaking classes yields valuable insights. The unanimous agreement among the interviewed students underscores the overall advantage of TikTok as an effective and versatile learning tool. Firstly, TikTok proves to be a valuable supplementary resource, providing diverse content that aids in better understanding study materials. Students emphasize that the platform's content enhances their comprehension, offering additional learning material that is both engaging and accessible. Secondly, TikTok's interactive features, such as stitch videos and duets, emerge as pivotal components that inject an engaging and enjoyable dimension into the learning process. Students express a strong preference for these features, highlighting their positive impact on the learning experience. Thirdly, TikTok significantly contributes to bolstering students' confidence in speaking English. The students' responses emphasize that the platform acts as a transformative space where they overcome initial apprehensions about fluency. Through consistent speaking practice, students report feeling more motivated and self-assured when communicating in English. Additionally, the analysis reflects a positive correlation between TikTok usage and increased motivation to learn English. The platform's dynamic and interactive nature contributes to a more stimulating learning environment, encouraging students to actively engage with the language. Furthermore, students note that TikTok facilitates a deeper understanding of English materials. The visual and auditory elements in TikTok videos enhance their comprehension and retention of vocabulary and pronunciation. Despite these positive aspects, it's essential to acknowledge potential drawbacks. Some students express concerns about distractions on TikTok, which may divert their focus from the intended educational content. This highlights the need for effective time management and self-discipline when using TikTok as a learning tool. In conclusion, the data-driven analysis reveals a multifaceted perspective on the advantages and disadvantages of using TikTok as an English learning tool. While it significantly contributes to supplementary learning, interactivity, and confidence-building, students need to navigate potential distractions. Ultimately, TikTok emerges as a valuable and effective tool in language education, requiring a balanced approach to optimize its benefits for English learners.